Management of Congenital Talipes Equino Varus by Ponseti Technique: Our Experience (Medicine Today, 2025)
Introduction: Clubfoot is a crippling ailment that can cause children to walk abnormally. The Ponseti treatment technique is utilized to treat children with congenital clubfoot. This study aims to determine the percentage of clubfoot children who benefit from the Ponseti approach and assess its efficacy. Objective: This research aims to assess the effectiveness of the Ponseti approach in the treatment of congenital Talipes Equino Varus (CTEV) in the neonatal age range. Materials and Methods: Between July 2022 and December 2022, a prospective observational study was conducted at the 250-bed municipal hospital in Gopalganj and the Sheikh Sayera Khatun Medical College hospital in Gopalganj. Every baby with CTEV was treated with Ponseti casting. Results: A total of 100 newborns and 155 CTEV feet were treated. There were thirty-four females and sixty-six males. There were sixty feet (38.71%) of non-rigid variety and ninety-five (61.29%) of stiff variation. 45 patients had unilateral involvement and 55 had bilateral involvement. The study group's mean pre-treatment Pirani score was 5.57. 150 feet (96.77%) of the 155 total feet were successfully managed. Conclusion: the Ponseti approach is a great, easy-to-use, minimally invasive method of treating CTEV deformity. Ideally, it can be performed as a day-case procedure without general anesthesia even in the neonatal period.Medicine Today 2025, Vol.37 (2): 209-213